How Field Relationships Shape Theorizing. (November 2019) - Blee, Kathleen
Field relationships shape the questions that researchers ask and the theories they develop. This article compares my interactions with research participants in a study of white supremacists with those in a study of mainstream grassroots activists. It demonstrates how expectations and negotiations with research participants affect theorizing by channeling what researchers are primed to see, what they notice, and what they understand as a puzzle to be investigated.